Evaluation of the Effectiveness of Groin Buildings Against Erosion on Ujong Blang Beach - Fran Cahya; Teuku Mudi Hafli; Fasdarsyah; Fadhliani; Nanda Savira Ersa; Yulia Prestika (Faculty of Engineering, Malikussaleh University, 2024)
Ujong Blang Beach is a dynamic area characterized by a variety of ecosystems. It serves a variety of purposes, including housing, tourism, and fishing. However, the coastline at Ujong Blang Beach, Lhokseumawe, is experiencing changes due to natural factors such as waves and sediment transport, causing erosion. This research aims to evaluate the erosivity and effectiveness of groyne structures in preventing erosion at Ujong Blang Beach. The methodology used involves 3D Delft numerical simulation using a grid size of 10 m x 10 m and a time period of 0.4 minutes. Input data for the Delft 3D simulation includes topography, bathymetry, tidal patterns, wave action, morphological factors, and sediment data. The simulation results show that Ujong Blang Beach experienced erosion, specifically, Region I Segment experienced erosion of around -40,277 meters, Segment II experienced erosion of around -29,122 meters, and Segment III experienced erosion of around -18,403 meters.